2008
DOI: 10.1590/s1413-70542008000200022
|View full text |Cite
|
Sign up to set email alerts
|

Sistema radicular de quatro porta-enxertos sob copa de tangerina 'Poncã'

Abstract: RESUMOEstudos realizados a campo sobre a extensão e a distribuição das raízes são importantes para a tomada de decisões referentes ao manejo das culturas. Objetivou-se com este trabalho estudar o sistema radicular dos porta-enxertos limão Cravo (Citrus limonia Osb.), limão Rugoso (Citrus jambhiri Lush.), tangerina Cleópatra (Citrus reticulata Blanco) e citrange C 13 [Citrus sinensis (L.) Osb. x Poncirus trifoliata (L.) Raf.], sob copa de tangerina Poncã (Citrus reticulata Blanco), com o método da trincheira. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
2
2
0
1
Order By: Relevance
“…In relation to effective depth (Figures 1 and 3), it was observed that up to 40 cm, 80% of the total root length were concentrated in all combinations evaluated and that, in the average of the six combinations, 83% of the root concentration were located in that depth, which is similar to result of Santana et al (2006) in citrus root distribution studies, who found 86% of the root concentration (cm.cm -3 of soil) located at depths of 0.0 to 38.0 cm and Neves et al, (2008), in a study on lime and lemon, who observed most of the roots at an effective depth of 36 cm and 41 cm, respectively.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In relation to effective depth (Figures 1 and 3), it was observed that up to 40 cm, 80% of the total root length were concentrated in all combinations evaluated and that, in the average of the six combinations, 83% of the root concentration were located in that depth, which is similar to result of Santana et al (2006) in citrus root distribution studies, who found 86% of the root concentration (cm.cm -3 of soil) located at depths of 0.0 to 38.0 cm and Neves et al, (2008), in a study on lime and lemon, who observed most of the roots at an effective depth of 36 cm and 41 cm, respectively.…”
Section: Resultssupporting
confidence: 76%
“…However, studies on the root system of plants are of great importance due to their role in sustaining and absorbing water and nutrients. Information on the distribution and extension of the root system of the different rootstocks are fundamental for decision making on cultural practices, especially those related to planting spacing, soil management, fertilization, irrigation and even the selection of materials adapted to a given region (Neves et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, with more time this cultivar can reach higher root development, as found by Dalal and Thakur (2011) in a 17-year-old pineapple orange trees grown on 'Cleopatra' mandarin, where this rootstock presented extensive lateral root system development, mostly in the upper layer 0-15 cm depth, and a dense However, with more time this cultivar can reach higher root development, as found by Dalal and Thakur (2011) in a 17-year-old pineapple orange trees grown on 'Cleopatra' mandarin, where this rootstock presented extensive lateral root system development, mostly in the upper layer 0-15 cm depth, and a dense and large canopy. A similar result was found by Neves et al (2008) who evaluated 12-year-old 'Ponkan' mandarin (C. reticulata Blanco) orchard and found that 'Cleopatra' mandarin had higher root length in the planting row (16.56 m) compared to 'Rangpur' lime (6.00 m), 'Rough' lime (5.70 m), and 'C13' citrange (4.49 m). PC 2 (Equation 2) showed more positive values than the other citrus rootstocks at 30 DAE for 'Troyer' and 'C13' citranges, and at 45 DAE for 'Troyer' citrange.…”
Section: Root Architecturesupporting
confidence: 82%
“…As raízes do 'Cravo', 'Cleópatra' e 'Trifoliata' seguiram a tendência observada por Neves et al (2004Neves et al ( , 2008. Nesses trabalhos a profundidade efetiva na entrelinha foi superior à profundidade efetiva na linha, indicando um maior aprofundamento do sistema radicular na região mais exposta ao sol, e, portanto mais exposta ao dessecamento, quando comparada com a linha de plantio, que fica abrigada na sombra das plantas e provavelmente com maior quantidade de água armazenada na superfície do solo.…”
Section: Resultsunclassified